Teaching Children About the Inverse Relation Between Addition and Subtraction - Nunes, T; Bryant, P; Hallett, D; Bell, D; Evans, D (2009)
Two intervention studies are described. Both were designed to study the effects of teaching children about the inverse relation between addition and subtraction. The interventions were successful with 8-year-old children in Study 1 and to a limited extent with 5-year-old children in Study 2. In Study 1 teaching children about inversion increased their success not just in Inverse problems (a + b- b = ?) but also in Transfer complement problems (a + b = c; c- b = ?).